Synthesis of intermediate compounds with P-N bond from (thio)carbamates and chlorodioxaphospholanes and -phosphorinanes and their reactivity - Murzin, Dmitry; Kolesova, Vera (European Journal of Chemistry, 2013)
A variety of 2-(N-alkoxy(thio)carbonyl alkyl(aryl)amino)-1,3,2-dioxaphospholanes and phosphorinanes were prepared from chlorodioxaphospholanes and phosphorinanes. Their structures were determined by IR, Mass and NMR spectroscopy. These compounds were employed in direct reactions with elemental sulphur and methylester of chloroacetic acid giving potentially physiologically active N-phosphorylated carbamates with P(O)-N and P(S)N bonds.